Association of biosurfactant production by indigenous bacteria isolated from petroleum contaminated soil with total petroleum hydrocarbon degradation - Azmi, Siti Norzilah; Mohd Shahrom, Amalia Sakina; Razali, Muhammad Aizat; Mohd Ashaari, Mardiana (2018)
Microbial biosurfactants are amphiphilic, surface-active compounds produced during biodegradation, increasing the bioavailability of organic pollutants such as hydrocarbons. This study aimed to determine the association between the ability of indigenous bacteria isolated from petroleum contaminated soil to produce biosurfactants with their ability to degrade total petroleum hydrocarbons (TPH). Four of these bacterial isolates (BSP1, BSP2, BSP3 and BSP4) were screened and characterized in terms of their potential in producing biosurfactants through qualitative and quantitative analysis; also supported by genetic characterization of the isolates by using molecular approach. These isolates exhibited some biosurfactant activities based on some qualitative (i.e emulsification assay) and quantitative screenings (i.e surface tension measurement). Highest emulsification activity exhibited by BSP4 (≈ 40 %) while for the rest of the isolates were between 22 to 27 %. Surface tension measurement confirmed the biosurfactant activity of the isolates, which were as low as ≈ 43 mN/m for BSP4 and BSP3. On the other hand, TPH biodegradation study was conducted for these four using GC-MS. Assuming growth-linked biodegradation; growth curves of these bacterial isolates showed the highest optical density reading after 36 hours of incubation and therefore suggesting rapid metabolism of hydrocarbons by the isolates within this timeframe. However, after seven days, biodegradation percentage of TPH showed the vice versa of the results for biosurfactant activities; BSP4 had the lowest TPH biodegradation percentage (≈ 28 %) although being the most potent in lowering surface tension. Meanwhile, BSP1 had the highest TPH biodegradation percentage (≈ 63 %) despite having the least biosurfactant activity measurements. Confirmation by genetic characterization revealed that isolates BSP3 had various genes encoding for biosurfactant synthesis (fenD, ituC and rhlAB) but none of the isolates had the ring-hydroxylating dioxygenase gene responsible in the initial step of TPH biodegradation. In conclusion, association of biosurfactant produced by indigenous bacteria isolated from petroleum contaminated soil with TPH biodegradation cannot be determined in this study. However, biosurfactants produced could be extracted and purified to be used in many industries and applications.